Composite Foams Prepared through Hollow Glass Microspheres Assisted Bubbling. Issue 1 (January 2013) - An, Zhenguo; Zhang, Jingjie
Composite foamy structures were prepared through hollow glass microspheres (HGM) assisted bubbling of silicone rubber with ammonium hydrogen carbonate as the blowing agent. The presence of HGM not only favoured the foaming process (acted as nucleating agent for the formation of minute bubbles at the initial stage of the bubbling), but also bring heterogeneous close-cell bubbles with stable inorganic shells into the foamy structure, which played an important part in the improvement of the heat insulation property of the product. Compared to the foamy structures without HGM, The composite foamy structures possessed improved heat insulation and sound absorbing properties. This work provides an additional strategy to fabricate composite foams with tailored cell structure and properties.